1971
DOI: 10.5951/at.18.5.0278
|View full text |Cite
|
Sign up to set email alerts
|

What's Your Position On… the role of experience in the learning of mathematics?

Abstract: Learning mathematics, like learning language and the aesthetic subjects, is an active process and should call into play our imaginative and creative powers so that the subject is a delight to pupils of all ages. Investigations of every aspect of mathematics—number knowledge itself and written calculations, as well as measures, shapes, and representations of all kinds—are included. In the title of this article, the word experience could very well be changed to investigations. Investigations, to me, cover a wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1973
1973
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The three participants' stories showed that they were deprived of learning mathematics due to passive approach to teaching-learning in the classroom and disconnection to their active working life in the day-today activities. According to Biggs and Hartung (1971), learning mathematics is a dynamic process that delights pupils in every aspect of mathematics, like number knowledge, measures, written calculation, shapes, etc. This activeness in the classroom process seemed lacking in the classrooms where the participants were studying.…”
Section: Discussionmentioning
confidence: 99%
“…The three participants' stories showed that they were deprived of learning mathematics due to passive approach to teaching-learning in the classroom and disconnection to their active working life in the day-today activities. According to Biggs and Hartung (1971), learning mathematics is a dynamic process that delights pupils in every aspect of mathematics, like number knowledge, measures, written calculation, shapes, etc. This activeness in the classroom process seemed lacking in the classrooms where the participants were studying.…”
Section: Discussionmentioning
confidence: 99%